Hubungan Pengetahuan tentang Antenatal Care (ANC) dengan Kepatuhan Kunjungan Antenatal Care (ANC) pada Ibu Hamil - Bunga Rahmatika Fedona; Lili Dariani; Siti Khadijah (Jurnal Bidan Mandiri, 2026)
Low coverage of antenatal care (ANC) visits remains a significant maternal health issue in Indonesia. The national K6 coverage reached 74.4%, which is still below the strategic target of 80%, while the coverage at Mungo Health Center was only 56.6%. One factor suspected to influence ANC visit compliance is the level of knowledge among pregnant women. This study aimed to analyze the relationship between knowledge of antenatal care and compliance with ANC visits among pregnant women in the Mungo Health Center working area in 2025. A quantitative study with a cross-sectional design was conducted involving 43 pregnant women selected from a population of 241 using area random sampling. Data were collected through questionnaires and documentation and analyzed using univariate and bivariate methods with the Chi-square test. The results showed that 58.1% of respondents had good knowledge of ANC and 60.5% complied with recommended ANC visits. Statistical analysis revealed a significant relationship between maternal knowledge and ANC visit compliance (p=0.006). Strengthening health education is essential to improve ANC compliance during pregnancy.